2022
DOI: 10.3389/fpsyg.2022.814348
|View full text |Cite
|
Sign up to set email alerts
|

New Working Capabilities for Coping With COVID Time Challenges

Abstract: The COVID-19 pandemic played as a booster to the cultural, social, and economic transformations triggered by the 4.0 Industrial Revolution, increasing the diffusion and employment of technological devices and requiring to reconsider the traditional approach to work and organization. Dealing with an emblematic organizational case, the article highlights the main key capabilities requested to face the current scenario, suggesting transformed attitudes needed to cope with the unfolding complex, uncertain, changin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 26 publications
4
11
0
Order By: Relevance
“…Having horizontal and boundary-less structures tends to increase the company’s shared vision (expert RealE), the organization’s malleability, permeability, and adaptability, the collaboration among employees, and support for co-creating transformation. In this context, we also perceive an orientation to ‘ multifunctional and self-managed team organization ’, which favors DT (following Matarazzo et al 2021 ) and, according to Fregnan et al ( 2022 ), promotes the integration of different kinds of knowledge which help to broaden perspectives and solutions. Likewise, promoting an innovation culture helps ‘cut bureaucracies’ (expert SysC) and ensure quality and agility in decision-making (experts EntF and SysJ).…”
Section: Resultsmentioning
confidence: 92%
See 4 more Smart Citations
“…Having horizontal and boundary-less structures tends to increase the company’s shared vision (expert RealE), the organization’s malleability, permeability, and adaptability, the collaboration among employees, and support for co-creating transformation. In this context, we also perceive an orientation to ‘ multifunctional and self-managed team organization ’, which favors DT (following Matarazzo et al 2021 ) and, according to Fregnan et al ( 2022 ), promotes the integration of different kinds of knowledge which help to broaden perspectives and solutions. Likewise, promoting an innovation culture helps ‘cut bureaucracies’ (expert SysC) and ensure quality and agility in decision-making (experts EntF and SysJ).…”
Section: Resultsmentioning
confidence: 92%
“…Besides, internal organizational collaboration and cooperation have been highlighted and explored as essential elements of DT (Fregnan et al 2022 ; Roblek et al 2021 ; Vial 2019 ; Li et al 2021 ). In this respect, all experts indicated that ‘ collaborative work execution’ supports DT’s success.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations